Sports Injuries of the Foot Evolving Diagnosis and Treatment - Philbin, Terrence M. (Springer US : Imprint: Springer, 2014)
Sports Injuries of the Foot is the go-to text for the management and treatment of foot injuries in athletes, demonstrating the current state-of-the-art techniques in assessment, testing and treatment. Organized anatomically beginning with the toes and working down the foot, it covers such common athletic injuries as turf toe, bunions, MTP instability, and midfoot and navicular fractures, all in the context of athletic activity. Attention is also given to special considerations for the adolescent and female athlete, with an eye toward return to play. Written by clinicians for clinicians, it will be an invaluable resource for orthopedists, podiatrists, team physicians, athletic trainers and primary care providers alike.